2011 Review of Conditionality : Outcomes of Fund-Supported Programs. (Policy Papers; Policy Paper ;, 2012)
This paper examines the effects of Fund-supported programs initiated during 2002-11, with special emphasis on programs started after the onset of the recent global economic crisis. The paper investigates the effects of Fund-supported programs on key macroeconomic variables and, data restrictions permitting, on social variables (social government spending, unemployment and social outcome indicators). Further, it analyzes the contribution of fiscal and external accommodation in helping program countries get through the recent global crisis. The assessment of the impact of Fund-supported programs is necessarily incomplete to the extent that the global financial crisis is ongoing and the most recent crisis programs such as the March 2012 program for Greece are not included. The Crisis Program Review provides detailed analysis of recent GRA-supported programs.